Fire safety of alcoholic beverages in retail stores. (26th February 2021) - Hakkarainen, Tuula; Korhonen, Timo; Vaari, Jukka
Summary: A fire test series to study pool fires of ethanol‐water mixtures in the small, intermediate and large scale has been performed. Additionally, demonstration tests of piles of PET plastic 0.5‐L liquor bottles (39 vol%) in retail store arrays were carried out to illustrate their burning behaviour. On the basis of the test results, the burning of pool fires of different alcoholic beverages and the fire load due to alcohol can be evaluated for the purpose of performance‐based fire safety design. The fire tests of retail store arrays showed that these fires grow slowly, and their heat release rate maxima are relatively low taking into account the mass of the fire load. The estimated heat release rate maxima of four‐layer retail store arrays were ca. 1.5 MW and their growth times were over 600 seconds. Design fires generally used for the fire safety design of shopping centres are typically much more severe than the fire test results of retail store arrays of alcoholic beverages in this study.